The Association of Hypertension With the Severity of and Mortality From the COVID-19 in the Early Stage of the Epidemic in Wuhan, China: A Multicenter Retrospective Cohort Study - Mubarik, Sumaira; Liu, Xiaoxue; Eshak, Ehab S.; Liu, Keyang; Liu, Qing; Wang, Fang; Shi, Fang; Wen, Haoyu; Bai, Jianjun; Yu, Chuanhua; Cao, Jinhong (Frontiers in Medicine, 2021)
Background Hypertension may affect the prognosis of COVID-19 illness. We analyzed the epidemiological and clinical characteristics associated with the disease severity and mortality in hypertensive versus non-hypertensive deceased COVID-19 patients. Methods We included all the deceased patients with laboratory-confirmed COVID-19 admitted to >200 health facilities in Wuhan between December 1 and February 24, 2020. The median survival time in COVID-19 patients with and without hypertension, the association of hypertension with the disease severity, and the risk factors associated with the COVID-19 mortality stratified by the hypertension status were assessed using the Kaplan-Meier survival analysis, logistic regression, and Cox proportional regression, respectively before and after the propensity score-matching (PS) for age and sex. Results The prevalence of hypertension in the studied 1833 COVID-19 patients was 40.5%. Patients with hypertension were more likely to have severe COVID-19 illness than patients without hypertension; the PS-matched multivariable-adjusted odds ratio (95% CI) was 2.44 (1.77-3.08). Moreover, the median survival time in the hypertension group was 3-5 days shorter than the non-hypertension group. There was a 2-fold increased risk of COVID-19 mortality in the hypertension group compared with the non-hypertension group; the PS-matched multivariable-adjusted hazard ratio (HR) = 2.04 (1.61-2.72), and the significant increased risk of COVID-19 mortality in the moderate versus mild COVID-19 illness was confined to patients with hypertension. Additionally, the history and the number of underlying chronic diseases, occupation, and residential location showed stronger associations with the COVID-19 mortality among patients with hypertension than patients without hypertension. Conclusion Hypertension was associated with the severity and mortality of COVID-19 illness.